INFLUENCE ANALYSES OF MACHINERY AND WORK FORCE PRODUCTION FACTOR TOWARD EPEXOL MEDICINE TABLET PRODUCTION - I Gusti Ngurah Agung Windra W. P.; Achmad Fudholi; Samsubar Saleh (Faculty of Pharmacy, Universitas Gadjah Mada)
Health is one of human wealth indicators so it becomes a priority in developing of a nation. Pharmaceutical industry is important to support that goal. This research was aimed to measure the influence of machinery and work force on production of Epexol tablet in PT. Sanbe Farma Bandung and to determine the most dominant variable. Data were collected retrospectively from production record batch of Epexol tablet in 2012. Data were analysed using a multiple linear regression followed transformation using Cobb-Douglass of production functional equation. Data were processed using SPSS software. A free variable influence towards dependent variables was analysed using an F-test and t-test with a confidence level of 95% (α = 0.05). The result showed that significant value of F-test was 0.0001, while significant value of t-test were 0.028 and 0.010 for machinery and work force variable respectively. An R determination coefficient value was 0.789, and R square was 0.623. It means that machinery and work force variables simultaneously influenced 62.3% of production of Epexol tablet. Cobb-Douglass equation function was Q =304979,55X10,039X20.059. In conclusion, there was a simultaneous and partial significant influence between machinery and work force variables towards total production of Epexol tablet. A dominant variable that affected in the number of Epexol production was a work force variable.Keywords: Machinery, Work force, Production, Epexol